Genito-urinary congenital malformations - Velásquez P., Humberto (2015)
Abnormalities congenital genital tract are relatively few compared with the number of ginecópatas treated in our department and even in other countries, as shown by our statistics and global. In our service we have found that from 1957 to 1963 found only 14 cases in a total of 2,716 consulted ginecópatas, ie 0.51%.